Factors influencing mothers' role in convulsion treatment among under-five children in lbadan, Nigeria (2009)
Convulsion among children between six months and five years is a major contributor to childhood mortality in less-developed societies, especially in sub-Saharan Africa. Most studies on under-five deaths have ignored the influence of socio-demographic and environmental factors as they relate to causes of the thematic health condition and available therapies. This study investigated mothers' perception of convulsion causation, relevant signs and symptoms, and the influence of socio-economic status on mothers' choice of remedies. The research was conducted in Ibadan, southwest Nigeria, which is densely populated with mainly Yoruba-speaking people. The study population comprised mothers who, at the time of fieldwork for the present analysis, had at least one under-five child. Five hundred questionnaire respondents were selected through a multistage sampling technique, and 14 in-depth interviews (lDls) were conducted among different categories of women identified through the snowball technique. Voluntary Social Action Theory and the Health Belief Model were used in explaining the relationship between the dependent and independent variables. The findings show that the remedies mothers chose were strongly influenced by socio-demographic factors such as marriage type, religion, level of education, occupation and place of residence. It is strongly suggested that interventions, health policies and programs should focus on how best to empower women to effectively utilize medical information that will enable them recognize symptoms of this common health condition and/or undertake preliminary therapies that contribute positively to convulsion prevention or treatment.